The possibility of cochlear synaptopathy in young people using a personal listening device - (:unkn) unknown (ELSEVIER SCI LTD, 2021)
Objective: To evaluate the association of listening to music loudly through personal listening devices with cochlear synaptopathy in young adults. Methods: Fifty healthy young adults selected among 109 volunteers were included in the study. Participants of high risk (n = 25) and low risk (n = 25) groups estimated according to ETDNL (estimated total daily noise level) were evaluated using pure tone audiometry, tympanometry, matrix test, electrocochleography (EcochG) and auditory brainstem response (ABR) to evaluate the occurrence of cochlear synaptopathy. Results: Audiometric thresholds between the groups were not significantly different (p > 0.05). High risk group participants showed poorer performance than the low-risk group on the TurMatrix test, in non-adaptive noise with-5 SNR and-7.5 SNR, and at the 50% understanding SNR level with headphones (p < 0.01). There was no difference in the adaptive free field in noise test at which 50% understanding was achieved (p > 0.05). The AP amplitudes on EcochG and wave V amplitudes on ABR were significantly smaller in the high-risk group (p < 0.05). There was no association between ETDNL and I/V ratio on ABR. Conclusion: Poorer performance in TurMatrix and other electrophysiologic tests revealed the negative effect of personal listening devices on the auditory system. Our findings support the hypothesis that personal listening devices could cause cochlear synaptopathy. Long-term studies are needed to determine the effects of binaural hearing and duration of noise exposure on the auditory system. (C) 2021 Oto-Rhino-Laryngological Society of Japan Inc. Published by Elsevier B.V. All rights reserved.
Keywords: Hidden hearing loss; ECochG; Cochlear synaptopathy; Speech-in-noise; BRAIN-STEM RESPONSE; HIDDEN HEARING-LOSS; IN-NOISE TESTS; TINNITUS; EXPOSURE; ADULTS